Is recovery of large-bodied zooplankton after nutrient loading reduction hampered by climate warming? A long-term study of shallow hypertrophic Lake Søbygaard, Denmark - Gutierrez, Marìa Florencia (2016)
Nutrient fluctuations and climate warming can synergistically affect trophic dynamics in lakes, resulting in enhanced symptoms of eutrophication, thereby potentially counteracting restoration measures. We performed a long-term study (23 years) of zooplankton in Danish Lake Søbygaard, which is in recovery after nutrient loading reduction, but now faces the effects of climate warming. We hypothesized that the recovery of large-bodied zooplankton after nutrient loading reduction would be hampered by climate warming through indirect effects on fish size structure. We found a shift in macrozooplankton from initial dominance of Daphnia spp. towards Bosmina spp. as well as a decline in the body size of copepods and an increase in the abundance of nauplii. These changes coincided with the increase in small sized fish as a result of rising water temperature. Despite a reduction in body size, the total biomass of cladocerans increased coinciding with a diminished fish catch per unit effort (CPUE), and likely then an overall reduction in the predation on zooplankton. A cascading effect to phytoplankton was evidenced by enhanced zooplankton:phytoplankton and cladoceran:phytoplankton ratios and a decrease in Chl-a:TP and Chl-a:TN ratios. Our results indicate that climate warming, through changes in the size structure of fish community, has major effects on zooplankton size structure. In Lake Søbygaard, the decline in zooplankton size did not prevent, but modulated, the positive cascading effect on phytoplankton through an expected diminished fish CPUE related to nutrient loading reduction.